Electrode assembly and manufacturing method thereof, and lithium secondary battery including the same
By optimizing the forming process of the anode active layer and forming an anode active layer with appropriate porosity, and forming a coating on its surface including polymer binder and polymer particles or ceramic particles with absolute zeta potential, the short circuit problem caused by the reduction of the separation membrane at high temperatures is solved, and the safety and energy density of the battery are improved.
Patent Information
- Application Number
- JP2024559645
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-05-30
- Filing Date
- 2023-05-31
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-05-31
AI Technical Summary
The separation membrane of existing lithium-ion batteries may shrink at high temperatures, resulting in short circuits between the anode and catal electrodes, increasing the risk of combustion and explosion. At the same time, the anode living layer is easily damaged during the coating formation process, affecting the safety and performance of the battery.
By optimizing the forming process of the anode active layer, a multiple curling step is used to form an anode active layer with appropriate porosity, and a coating including polymer binder and polymer particles or ceramic particles with absolute zeta potential is formed on its surface, controlling the thickness of the coating below 15 microns.
It effectively prevents damage to the anode active layer during the coating forming process, ensures the appropriate porosity and mechanical properties of the anode active layer and coating, improves the safety and energy density of lithium-ion batteries, and reduces the risk of short circuits.
Smart Images

Figure 2025511954000001_ABST
Abstract
Description
[Technical field]
[0001] Cross-reference of related applications (etc.) This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0067846 filed on June 2, 2022 and Korean Patent Application No. 10-2023-0069510 filed on May 30, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to an electrode assembly, a manufacturing method thereof, and a lithium secondary battery including the same. [Background technology]
[0003] Recently, the application areas of lithium secondary batteries have been rapidly expanding from power supply for electronic devices such as electrical, electronic, communication, and computer equipment to power storage supply for large-area devices such as automobiles and power storage devices, and as a result, there is an increasing demand for lithium secondary batteries with high capacity, high output, long life, and high stability.
[0004] Lithium secondary batteries are generally composed of a positive electrode, a negative electrode, a separator, and an electrolyte, and are known in the art to include a positive electrode that can generate oxygen due to an unstable structure in a charged state. Since the generation of oxygen increases the risk of fire, research and development is being conducted on methods to improve the safety of lithium secondary batteries.
[0005] For example, a typical separator included in an existing lithium secondary battery, such as a polyolefin-based porous separator, may shrink at high temperatures, and such shrinkage of the separator may cause a short circuit between the positive and negative electrodes. When such a short circuit occurs, the risk of fire may further increase due to the interaction with oxygen generated by the unstable positive electrode.
[0006] In order to reduce the risk of fire and improve the safety of the lithium secondary battery, a lithium secondary battery including a porous coating layer interposed between the positive electrode and the negative electrode to replace or supplement the separator may be considered. The porous coating layer allows ions to move between the positive electrode and the negative electrode while electrically insulating the positive electrode and the negative electrode from each other.
[0007] However, during the process of forming a coating layer on the positive or negative electrode, the medium of the composition for forming the coating layer may be impregnated into the positive electrode, causing problems such as swelling of the electrode active material layer, and the additional formation of the coating layer may make it difficult to achieve an appropriate porosity of the positive electrode active material layer, or the active material layer may be broken during the process of forming the coating layer.
[0008] In consideration of these problems, there is a continuing need to develop a technology that can effectively form a porous coating layer that replaces or supplements a separator on an electrode to improve the safety of the secondary battery while solving the problems associated with the coating layer formation process. Summary of the Invention [Problem to be solved by the invention]
[0009] Therefore, the present invention provides an electrode assembly and a manufacturing method thereof, which can improve the safety of a secondary battery by forming a good porous coating layer on a positive electrode active material layer, while suppressing problems such as damage to the positive electrode active material layer during the process of forming the porous coating layer.
[0010] The present invention also provides a lithium secondary battery including the electrode assembly and having improved safety. [Means for solving the problem]
[0011] One embodiment of the invention provides a method for manufacturing an electrode assembly, the method including: (S1) applying a positive electrode slurry onto a positive electrode current collector and drying the slurry to form a positive electrode active material layer; (S2) performing a primary rolling of the positive electrode current collector and the positive electrode active material layer; (S3) applying a coating layer slurry onto the positive electrode active material layer and drying the slurry to form a positive electrode laminate including a coating layer; (S4) performing a secondary rolling of the positive electrode laminate; and (S5) laminating a negative electrode on the coating layer to manufacture an electrode assembly, wherein the primary rolling step is performed such that a porosity of the positive electrode active material layer is 35% to 45%, and the secondary rolling step is performed such that a porosity of the positive electrode active material layer is 20% to 30%.
[0012] In another embodiment of the present invention, there is provided an electrode assembly including a positive electrode current collector, a positive electrode active material layer disposed on the positive electrode current collector, a coating layer coated on the positive electrode active material layer, a mixed layer in which the positive electrode active material layer and the coating layer are mixed, and a negative electrode disposed on the coating layer, the negative electrode current collector and the negative electrode active material layer, the coating layer and the mixed layer including a polymer binder and polymer particles or ceramic particles having an absolute value of a zeta potential of 25 mV or more dispersed on the polymer binder, and a thickness of the mixed layer is less than 15 μm.
[0013] Another embodiment of the present invention provides a lithium secondary battery including a battery case, a flame-retardant solvent having a flash point of 100°C or more or having no flash point, a flame-retardant electrolyte including a lithium salt, and the electrode assembly. Effect of the Invention
[0014] According to the present invention, a process for forming a porous coating layer on a positive electrode active material layer is optimized to suppress damage to the positive electrode during the formation of the coating layer, while a porous coating layer that replaces or supplements an existing separator can be well formed on the positive electrode active material layer, and appropriate porosity and mechanical properties of the positive electrode active material layer and the porous coating layer can be achieved.
[0015] As a result, this can greatly contribute to the development of lithium secondary batteries that exhibit improved safety while also having high capacity characteristics and energy density. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a photograph of the cross section of the positive electrode active material layer and the coating layer of Example 1 observed through a scanning electron microscope (SEM). [Diagram 2] FIG. 2 is a photograph of a cross section of the positive electrode active material layer and the coating layer of Comparative Example 4 observed through a scanning electron microscope (SEM). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, the terms and words used in this specification and claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that is consistent with the technical idea of the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his or her invention.
[0018] Unless otherwise defined, all terms (including technical and scientific terms) used herein may be used in a manner commonly understood by those having ordinary skill in the art to which the present invention belongs. Furthermore, terms defined in commonly used dictionaries are not to be interpreted ideally or excessively unless otherwise clearly and specifically defined.
[0019] The terms used in the present specification are intended to describe the embodiments and are not intended to limit the present invention. In the present specification, the singular form includes the plural form unless otherwise specified in the text. The terms "comprises" and / or "comprising" used in the specification do not exclude the presence or addition of one or more other components other than the components mentioned.
[0020] In this specification, when a part includes a certain component, this does not mean to exclude other components, unless specifically stated to the contrary, but means that it may further include other components.
[0021] In this specification, the phrase "A and / or B" means A or B or A and B.
[0022] Manufacturing method of electrode assembly A method for manufacturing an electrode assembly according to an embodiment of the invention includes the steps of: (S1) applying a positive electrode slurry onto a positive electrode current collector and drying it to form a positive electrode active material layer; (S2) performing a primary rolling of the positive electrode current collector and the positive electrode active material layer; (S3) applying a coating layer slurry onto the positive electrode active material layer and drying it to form a positive electrode laminate including a coating layer; (S4) performing a secondary rolling of the positive electrode laminate; and (S5) laminating a negative electrode on the coating layer to manufacture an electrode assembly, wherein the primary rolling step may be performed such that a porosity of the positive electrode active material layer is 35% to 45%, and the secondary rolling step may be performed such that a porosity of the positive electrode active material layer is 20% to 30%.
[0023] In the method for manufacturing the electrode assembly, the coating layer slurry may include, for example, a polymer binder and polymer particles or ceramic particles having an absolute value of a zeta potential of 25 mV or more dispersed on the polymer binder, and may enable the movement of lithium ions during charging and discharging while electrically insulating the positive and negative electrodes.
[0024] In the manufacturing method of the present embodiment, when forming the porous coating layer that replaces or supplements the existing separator, the positive electrode active material layer and the porous coating layer are formed through multiple rolling steps. It has been confirmed that this process allows a mixed layer in which a portion of the porous coating layer permeates and mixes with the positive electrode active material layer to be formed with a very thin thickness.
[0025] The formation of such a thin porous coating layer can prevent short circuits or fires between electrodes due to thermal shrinkage of the separator, and the thin thickness of the porous coating layer can further increase the energy density of the unit secondary battery.
[0026] In addition, the multiple rolling steps can achieve a porosity suitable for the final positive electrode active material layer, for example, a porosity of 20% to 30%, while preventing the positive electrode active material layer from being damaged by a higher pressure in the rolling step for forming the coating layer, etc. In addition, the multiple rolling steps can reduce a problem of swelling of the positive electrode active material layer by the liquid medium of the coating layer slurry.
[0027] Meanwhile, each component of the electrode assembly will be specifically described in the following description of the electrode assembly, and each step of the manufacturing method will be described below.
[0028] First, a positive electrode slurry is applied onto a positive electrode current collector and dried to form a positive electrode active material layer (S1).
[0029] The positive electrode slurry may be prepared by dissolving or dispersing a positive electrode active material, a binder, a conductive material, and an optional dispersant in a solvent.
[0030] The positive electrode slurry may be coated on a positive electrode current collector and dried to form a positive electrode active material layer. For example, the positive electrode slurry may be coated on a positive electrode current collector, and the positive electrode current collector and the positive electrode slurry may be dried by passing through a drying area equipped with an exhaust fan at a constant speed in a continuous process. The drying area may be divided into six areas with a length of about 2 m, and the temperature in each drying area may be about 50 to 95°C.
[0031] Thereafter, the positive electrode current collector and the positive electrode active material layer are subjected to a primary rolling (S2).
[0032] Such a first rolling step and a second rolling step described later can be performed, for example, by using rolling rolls, and the thickness and / or porosity of the positive electrode current collector and the positive electrode active material layer can be controlled by appropriately setting the gap between the rolling rolls.
[0033] The thickness and / or porosity of the positive electrode current collector and the positive electrode active material layer can be changed within a suitable range by the first rolling process.
[0034] After such primary rolling, the total thickness of the primarily rolled positive electrode current collector and the positive electrode active material layer may be 80% to 90%, or 83% to 87% of the total thickness of the non-rolled positive electrode current collector and the positive electrode active material layer before the primary rolling.
[0035] If the thickness ratio after the first rolling is less than 80% of the initial thickness, the positive electrode current collector and the positive electrode active material layer are excessively rolled, which may cause damage such as wavyness of the positive electrode active material layer on the positive electrode current collector. On the other hand, if the thickness ratio after the first rolling is more than 90% of the initial thickness, the positive electrode current collector and the positive electrode active material layer are not substantially rolled, which may cause the liquid medium of the coating layer slurry to permeate into the positive electrode active material layer in the subsequent steps, which may cause swelling.
[0036] In a specific example, in an initial state before the primary rolling, the total thickness of the positive electrode current collector and the positive electrode active material layer may be 150 to 200 μm, or 160 to 180 μm, and the total thickness of the positive electrode current collector and the positive electrode active material layer after the primary rolling may be 120 to 180 μm, or 130 to 170 μm.
[0037] In addition, the first rolling step can be performed by passing the positive electrode current collector and the positive electrode active material layer between the rolling rolls so that the porosity of the positive electrode active material layer is 35% to 45%, or 37% to 43%.
[0038] Here, the porosity (P, unit: %) of the positive electrode active material layer can be calculated by a method commonly used in the art, specifically, by the following Equation 1:
[0039] [Formula 1] P = (1-D) / T x 100 In the above formula 1, D is the density of the positive electrode active material layer, and T is the true density of the positive electrode active material excluding the current collector in the positive electrode. The true density refers to the inherent density of the positive electrode active material without voids.
[0040] The density D of the positive electrode active material layer can be calculated by the following formula 2.
[0041] [Formula 2] D = M / (S × H) In the above formula 2, M is the mass of the positive electrode active material layer, S is the area of the positive electrode active material layer, and H is the thickness of the positive electrode active material layer.
[0042] If the porosity of the positive electrode active material layer after the first rolling is less than 35%, the positive electrode current collector and the positive electrode active material layer may be excessively rolled, and damage such as wavy positive electrode active material layer on the positive electrode current collector may occur. On the other hand, if the porosity of the positive electrode active material layer after the first rolling exceeds 45%, the positive electrode current collector and the positive electrode active material layer may not be substantially rolled, and the liquid medium of the coating layer slurry may permeate the positive electrode active material layer in the subsequent step, and swelling may occur. In addition, the permeation of the liquid medium contained in the coating layer slurry may increase the porosity of the positive electrode active material layer, and non-uniform pores may be formed.
[0043] Thereafter, a coating layer slurry is applied onto the positive electrode active material layer and dried to form a positive electrode laminate including a coating layer (S3).
[0044] The coating layer slurry may be, for example, a slurry composition including a polymer binder, polymer particles or ceramic particles having an absolute value of a zeta potential of 25 mV or more, and a liquid medium, and may be used to form a porous coating layer (including a mixed layer) on the positive electrode active material layer.
[0045] At this time, the zeta potential of the polymer particles or ceramic particles is a physical property that reflects the surface polarity of the particles and defines the electrostatic repulsion or dispersibility between the particles, and the polymer particles or ceramic particles having a large absolute value of the zeta potential can be uniformly dispersed on the positive electrode active material layer to exhibit good and uniform coating properties, and a large number of fine and uniform pores that allow lithium ions to pass between the particles can be defined. In addition, the particles that satisfy this zeta potential can make the porous coating layer exhibit excellent impregnation with a flame-retardant electrolyte containing a flame-retardant solvent. The combination of the porous coating layer and the flame-retardant electrolyte can make the lithium secondary battery exhibit better safety.
[0046] The zeta potential of the polymer particles or ceramic particles can be measured by, for example, an electrophoretic light scattering method using a dynamic light scattering device. In this case, the zeta potential of the polymer particles or ceramic particles can be measured in a state where the polymer particles or ceramic particles are dispersed in water or an alcohol-based solvent without a separate dispersant. In a specific example, the zeta potential can be measured in a state where the polymer particles or ceramic particles are dispersed in a water solvent at a concentration of 0.1 wt % or less.
[0047] The absolute value of the zeta potential of the polymer particles or ceramic particles may be 25 mV or more, 35 mV or more, or 45 mV or more, and may be 100 mV or less, 90 mV or less, or 80 mV or less. Within such a range, good coating properties of the coating layer slurry can be achieved, and high impregnation of the flame-retardant electrolyte can be ensured.
[0048] Specific examples of the polymer particles include one or more selected from the group consisting of polymethyl (meth)acrylate, polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate, polyethylene terephthalate, and polyphenylene sulfide.
[0049] Specific examples of the ceramic particles include one or more selected from the group consisting of boehmite, aluminum oxide, titanium oxide, iron oxide, silicon oxide, zirconium oxide, cobalt oxide, tin oxide, nickel oxide, zinc oxide, vanadium oxide, and manganese oxide.
[0050] The zeta potential of the polymer particles or ceramic particles can be adjusted not only by the type of each particle but also by the particle size or surface properties of the particles. Thus, in order to achieve the zeta potential, dispersibility, or appropriate porosity of the porous coating layer of the polymer particles or ceramic particles, the polymer particles or ceramic particles may have a particle size of 50 nm to 3 μm, or 50 nm to 1.5 μm, or 100 nm to 1 μm.
[0051] In addition, in order to control the surface properties of the polymer particles or ceramic particles and thereby adjust the zeta potential, the polymer particles or ceramic particles may be included in the coating layer slurry in a state where they are surface-treated with oxygen plasma or ion beam.
[0052] Meanwhile, in the coating layer slurry, the polymer binder may be the same polymer as the binder contained in the positive electrode active material layer, and specific examples thereof include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene (PE), polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, nitrile rubber, styrene-butadiene rubber, and fluororubber, and a mixture or copolymer of two or more selected from these may be used. However, the specific composition of the polymer binder can be determined by a person skilled in the art in consideration of the type and characteristics of the polymer particles or ceramic particles, the method of forming the coating layer, and the like.
[0053] In addition, in consideration of the good coating properties of the coating layer slurry and the good dispersibility of the particles, the coating layer slurry may contain the polymer binder:polymer particles or ceramic particles in a weight ratio of 5:95 to 40:60, or 10:90 to 35:65.
[0054] The coating layer slurry may further include a dispersant, and such a dispersant may include, for example, at least one of hydrogenated nitrile rubber (H-NBR) and tannic acid.
[0055] The coating layer slurry further includes a liquid medium for dispersing the above-mentioned components. Such a medium may include an organic solvent such as N-methyl-2-pyrrolidone (NMP) or acetone, or water, and may be appropriately selected in consideration of the types of the above-mentioned polymer particles, ceramic particles, or polymer binder.
[0056] The coating layer slurry may be applied onto the first rolled positive electrode active material layer and dried to form a porous coating layer on the positive electrode active material layer, and the resultant product may be defined as a positive electrode laminate.
[0057] Meanwhile, after the formation of the porous coating layer, the positive electrode laminate is subjected to a second rolling (S4). The second rolling process can be performed by appropriately setting the gap between the rolls, similar to the first rolling process, and the thickness and / or porosity of the positive electrode active material layer and the porous coating layer can be appropriately achieved by the second rolling process.
[0058] After the second rolling, the total thickness of the second-rolled positive electrode current collector and the positive electrode active material layer may be 60% to 75%, or 63% to 72% of the total thickness of the unrolled positive electrode current collector and the positive electrode active material layer before the first rolling. In this case, the thickness of the second-rolled positive electrode active material layer may be calculated taking into consideration the thickness of a mixed layer containing the porous coating layer, and the thickness of each layer may be confirmed through an electron microscope analysis, etc.
[0059] If the thickness ratio after the second rolling is less than 60% of the initial thickness, the positive electrode laminate is excessively rolled, and the thickness of the porous coating layer becomes too thin, so that the positive electrode and the negative electrode may easily be short-circuited or the positive electrode active material layer may be damaged. On the other hand, if the thickness ratio after the second rolling exceeds 75% of the initial thickness, the positive electrode active material layer may not have an appropriate porosity, and the battery characteristics may be deteriorated.
[0060] The second rolling step may be performed by passing the positive electrode laminate between the rolling rolls so that the porosity of the positive electrode active material layer is 20% to 30%, or 22% to 28%.
[0061] If the porosity of the positive electrode active material layer after the second rolling is less than 20%, the positive electrode laminate is excessively rolled, and the thickness of the porous coating layer becomes too thin, so that the positive electrode and the negative electrode may easily be short-circuited or the positive electrode active material layer may be damaged. On the other hand, if the porosity of the positive electrode active material layer after the second rolling exceeds 30%, the positive electrode active material layer may not have an appropriate porosity, and the capacity characteristics of the battery may be reduced.
[0062] Then, a negative electrode is laminated on the porous coating layer to manufacture an electrode assembly (S5).
[0063] The negative electrode may include a negative electrode current collector and a negative electrode active material layer, as described below. Also, in the electrode assembly manufacturing step, the electrode assembly may be manufactured by stacking the negative electrode on the porous coating layer in a state where the porous coating layer is formed on the upper surface of the second rolled positive electrode laminate.
[0064] Hereinafter, an example of an electrode assembly that can be manufactured by the method of the embodiment will be described in detail.
[0065] electrode assembly According to another embodiment of the present invention, there is provided an electrode assembly including a positive electrode current collector, a positive electrode active material layer disposed on the positive electrode current collector, a coating layer coated on the positive electrode active material layer, a mixed layer in which the positive electrode active material layer and the coating layer are mixed, and a negative electrode disposed on the coating layer and including a negative electrode current collector and a negative electrode active material layer, wherein the coating layer and the mixed layer include a polymer binder, and polymer particles or ceramic particles having an absolute value of a zeta potential of 25 mV or more dispersed on the polymer binder, and the mixed layer may have a thickness of less than 15 μm.
[0066] The coating layer may be a porous coating layer having a plurality of pores with a diameter of, for example, 10 nm or more and a porosity equivalent to that of the positive electrode active material layer. Such a porous coating layer can replace or supplement an existing separator by electrically insulating the positive electrode and the negative electrode and allowing the movement of lithium ions during charging and discharging.
[0067] In the electrode assembly of the other embodiment, the formation of the porous coating layer can prevent short circuit or ignition between electrodes due to thermal shrinkage of the existing separator, etc., thereby providing a lithium secondary battery with improved safety. In addition, the minimal formation of the mixed layer allows the porous coating layer to have a thinner thickness, thereby further increasing the energy density of the unit secondary battery.
[0068] In the electrode assembly of this other embodiment, the thickness of the mixed layer may be 0 μm or more and less than 15 μm, 0.1 μm or more and less than 10 μm, or 1 μm or more and less than 5 μm, specifically, 5 μm to 14 μm, or 7 μm to 12 μm. The thickness of the mixed layer may be adjusted by controlling the degree of the first rolling described above.
[0069] Specifically, the primary rolling is performed so that the total thickness of the primary-rolled cathode current collector and the cathode active material layer is 80% to 90% of the total thickness of the non-rolled cathode current collector and the cathode active material layer, thereby achieving the minimum thickness of the mixed layer. Also, the primary rolling process is performed so that the porosity of the cathode active material layer is 35% to 45%, thereby achieving the minimum thickness of the mixed layer during the secondary rolling.
[0070] When the thickness of the mixed layer satisfies the above numerical range, the thickness of the porous coating layer replacing or supporting the separator can be made thin, thereby improving the coating property for the positive electrode active material layer. In addition, the porosity and electrical properties of the positive electrode active material layer can be adjusted to desired ranges by controlling the thickness of the porous coating layer.
[0071] Meanwhile, the compositions of the mixed layer and the porous coating layer are the same as those described in the manufacturing method of the embodiment, so further description thereof will be omitted.
[0072] In the electrode assembly, the positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has electrical conductivity. For example, the current collector may be stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like. Such a positive electrode current collector may have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the positive electrode current collector to increase the adhesive strength to the positive electrode active material layer. For example, the positive electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0073] The positive electrode active material layer on the positive electrode current collector may contain a positive electrode active material, and may further contain a conductive material, a binder, and the like, as necessary.
[0074] The positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium, and specifically, may include a lithium metal oxide containing one or more metals such as cobalt, manganese, nickel, or aluminum and lithium. More specifically, the lithium metal oxide is a lithium-manganese-based oxide (for example, LiMnO2, LiMn2O4, etc.), a lithium-cobalt-based oxide (for example, LiCoO2, etc.), a lithium-nickel-based oxide (for example, LiNiO2, etc.), a lithium-nickel-manganese-based oxide (for example, LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-Z Ni Z O4 (where 0 < Z < 2), etc.), a lithium-nickel-cobalt-based oxide (for example, LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1), etc.), a lithium-manganese-cobalt-based oxide (for example, LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-Z1 Co Z1 O4 (where 0 < Z1 < 2), etc.), a lithium-nickel-manganese-cobalt-based oxide (for example, Li(Ni p Co q Mn r )O2 (where 0 < p < 1, 0 < q < 1, 0 < r < 1, p + q + r = 1) or Li(Ni p1 Co q1 Mn r1 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r1 < 2, p1 + q1 + r1 = 2), etc.) or a lithium-nickel-cobalt-transition metal (M) oxide (for example, Li(Ni p2 Co q2 Mn r2 M s2)O2 (where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo; p2, q2, r2, and s2 are each atomic fractions of independent elements, 0 < p2 < 1, 0 < q2 < 1, 0 < r2 < 1, 0 < s2 < 1, and p2 + q2 + r2 + s2 = 1), etc.), and one or more of these compounds may be included.
[0075] Among these, in terms of being able to enhance the capacity characteristics and safety of the battery, the lithium metal oxide is LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (e.g., Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.), lithium nickel cobalt aluminum oxide (e.g., Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.), or lithium nickel manganese cobalt aluminum oxide (e.g., Li(Ni 0.86 Co 0.05 Mn 0.07 Al 0.02 )O2), etc., and one or more mixtures of these may be used.
[0076] The positive electrode active material may be contained at 60 to 99% by weight, or 70 to 99% by weight, or 80 to 98% by weight based on the total weight of the positive electrode active material layer.
[0077] In addition, the conductive material is a component for further improving the conductivity of the positive electrode active material, and such a conductive material is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, carbon powders such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; graphite powders such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fibers such as carbon fibers and metal fibers; carbon fluoride powder; conductive powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives may be used.
[0078] Typically, the conductive material may be included in an amount of 1 to 20 wt %, or 1 to 15 wt %, or 1 to 10 wt %, based on the total weight of the positive electrode active material layer.
[0079] On the other hand, the binder is a component that assists in binding the positive electrode active material to the conductive material and the like and in binding the positive electrode current collector.
[0080] Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene (PE), polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, various copolymers, and the like.
[0081] Typically, the binder may be included in an amount of 1 to 20 wt %, or 1 to 15 wt %, or 1 to 10 wt %, based on the total weight of the positive electrode active material layer.
[0082] Meanwhile, the negative electrode may include a negative electrode current collector and a negative electrode active material layer.
[0083] The negative electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, or the like, an aluminum-cadmium alloy, or the like may be used.
[0084] The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and may have fine irregularities on its surface to enhance the binding force of the negative electrode active material, as in the case of the positive electrode current collector. For example, the negative electrode current collector may be used in various forms, such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.
[0085] The negative electrode active material layer may contain a negative electrode active material, and may further contain a conductive material, a binder, and the like, as necessary.
[0086] The negative electrode active material may include at least one selected from the group consisting of lithium metal, a carbon material capable of reversibly intercalating / deintercalating lithium ions, a metal or an alloy of such a metal and lithium, a metal composite oxide, a material capable of doping and dedoping lithium, and a transition metal oxide.
[0087] The carbonaceous material capable of reversibly intercalating / deintercalating lithium ions may be any carbonaceous negative electrode active material commonly used in lithium ion secondary batteries, and representative examples thereof include crystalline carbon, amorphous carbon, or both. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon (low-temperature calcined carbon), hard carbon, mesophase peach carbide, calcined coke, etc.
[0088] As the metal or an alloy of these metals and lithium, a metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn, or an alloy of these metals and lithium may be used.
[0089] As the metal composite oxide, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3(0 < x ≦ 1), Li x WO2(0 < x ≦ 1) and Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x < 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8) may be selected from the group consisting of and used.
[0090] As the substance capable of doping and undoping lithium, Si, SiO x (0 < x ≦ 2), Si-Y alloy (wherein Y is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth element and a combination thereof, and is not Si), Sn, SnO2, Sn-Y (wherein Y is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth element and a combination thereof, and is not Sn), etc. may be mentioned, and at least one of these and SiO2 may be mixed and used. As the element Y, it may be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po and a combination thereof.
[0091] Examples of the transition metal oxide include lithium-containing titanium oxide (LTO), vanadium oxide, and lithium vanadium oxide.
[0092] The negative electrode active material may be included in an amount of 60 to 99 wt %, 70 to 99 wt %, or 80 to 98 wt %, based on the total weight of the negative electrode active material layer.
[0093] Meanwhile, the types and amounts of the binder and conductive material that may be included in the negative electrode active material layer are substantially the same as those described above for the positive electrode active material layer, and therefore, further description thereof will be omitted.
[0094] Lithium secondary battery According to a further embodiment of the present invention, there is provided a lithium secondary battery including a battery case, a flame-retardant solvent having a flash point of 100°C or more or no flash point, a flame-retardant electrolyte including a lithium salt, and the electrode assembly described above.
[0095] The lithium secondary battery includes an electrode assembly including the porous coating layer and a flame-retardant electrolyte including a flame-retardant solvent. As described above, the porous coating layer includes polymer particles or ceramic particles having certain properties and can exhibit excellent impregnation with the flame-retardant solvent and electrolyte. Therefore, the combination of the porous coating layer and the flame-retardant electrolyte can more effectively prevent ignition due to a short circuit between the electrodes, further improving the safety of the lithium secondary battery and achieving excellent electrical properties.
[0096] Such a flame-retardant solvent is a solvent having low volatility and flammability, and can be defined by a certain flash point. For example, the flame-retardant solvent can include organic solvents that are substantially non-flammable and have no flash point, and organic solvents having a high flash point of 100°C or more, or 100 to 250°C, or 110 to 200°C, and low volatility. The lithium secondary battery including such a flame-retardant solvent and a flame-retardant electrolyte containing a lithium salt can exhibit excellent safety and stability. In addition, since the flame-retardant electrolyte can be uniformly impregnated into the porous coating layer, the lithium secondary battery can have excellent electrochemical properties. The flash point defining the flame-retardant solvent can be measured by a closed or open method according to the standard method of ASTM D93 or ASTM D1310.
[0097] In a specific example, the flame-retardant solvent may be an organic solvent having a functional group that can contribute to low volatility and flame retardancy or non-flammability, for example, a functional group selected from the group consisting of a sulfone-based functional group, a fluorine-containing functional group such as a fluorine-substituted hydrocarbon group, a phosphorus-containing functional group such as a phosphate group or a phosphonate group, and a nitrile-based functional group, or one or more of such organic solvents may be mixed and used. More specifically, the flame-retardant solvent may include one or more organic solvents selected from the group consisting of a sulfone-based compound, a nitrile-based compound, a phosphoric acid-based compound, and a carbonate-based compound substituted with fluorine.
[0098] Among these, the sulfone-based compound may be a cyclic sulfone-based compound or a linear sulfone-based compound, and specifically may include one or more selected from the group consisting of sulfolane, ethyl methyl sulfone, dibutyl sulfone, ethyl vinyl sulfone, methyl propyl sulfone, ethyl-i-propyl sulfone, ethyl-i-butyl sulfone, i-propyl-i-butyl sulfone, i-propyl-s-butyl sulfone, and butyl-i-butyl sulfone.
[0099] The nitrile compound may include at least one selected from the group consisting of malononitrile, succinonitrile, glutaronitrile, adiponitrile, suberonitrile, and sebaconitrile.
[0100] The phosphoric acid compound may include at least one selected from the group consisting of dimethyl methyl phosphate, trimethyl phosphate, triethyl phosphate, tributyl phosphate, diethyl ethyl phosphate, dimethyl methyl phosphate, dimethyl (2-methoxyethoxy) methyl phosphonate, diethyl (2-methoxyethoxy) methyl phosphonate, and triphenyl phosphate.
[0101] In addition, the fluorine-substituted carbonate-based compound is bis(2,2,3,3-tetrafluoropropyl)carbonate, methyl-2,2,2-trifluoroethyl carbonate, ethyl-2,2,2-trifluoroethyl carbonate, propyl-2,2,2-trifluoroethyl carbonate, methyl-2,2,2,2',2',2'-hexafluoro-i-propyl carbonate, ethyl-2,2,2,2',2',2'-hexafluoro-i-propyl carbonate, The carbonate may include one or more selected from the group consisting of difluoro-i-propyl carbonate, di-2,2,2-trifluoroethyl carbonate, 2,2,2-trifluoroethyl-N,N-dimethyl carbonate, hexafluoro-i-propyl-N,N-dimethyl carbonate, 4-(2,2,3,3-tetrafluoropropoxymethyl)-[1,3]-dioxolan-2-one, and bis(2,2,3,3-pentafluoropropyl)carbonate.
[0102] On the other hand, the lithium salt contained in the flame-retardant electrolyte is used as a medium for transferring ions within the lithium secondary battery.
[0103] Lithium salts, for example, have Li as the cation. + Including F - , Cl - , Br - , I - , NO3- , N(CN)2 - , BF4 - , ClO4 - , B 10 Cl 10 - , AlCl4 - , AlO2 - , PF6 - , CF3SO3 - , CH3CO2 - , CF3CO2 - , AsF6 - , SbF6 - , CH3SO3 - , (CF3CF2SO2)2N - , (CF3SO2)2N - , (FSO2)2N - , BF2C2O4 - , BC4O8 - , PF4C2O4 - , PF2C4O8 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , C4F9SO3 - , CF3CF2SO3 - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , CF3(CF2)7SO3 - and SCN - The anion may also include an anion selected from the group consisting of:
[0104] Specifically, the lithium salt is LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10, LiAlCl4, LiAlO2, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiFSI (lithium bis(fluorosulfonyl)imide, LiN(SO2F)2), LiBETI (lithium bis(perfluoroethanesulfonyl)imide, LiN(SO2CF2CF3)2, and LiTFSI (lithium bis(trifluoromethanesulfonyl)imide, LiN(SO2CF3)2), but those containing LiN(SO2CF3)2 are preferred in consideration of excellent stability. In addition to these, lithium salts commonly used in electrolytes for lithium secondary batteries can be used without any particular restriction.
[0105] The concentration of the lithium salt can be appropriately changed within a range that can be normally used, but in order to obtain an optimal effect of forming a coating for preventing corrosion on the electrode surface, the lithium salt may be contained in the flame-retardant electrolyte at a concentration of 0.5 M to 6 M, or 1 M to 3 M, or 1 M to 2.5 M. When the concentration of the lithium salt satisfies the above range, the effect of improving the cycle characteristics during high-temperature storage of the lithium secondary battery is sufficient, and the viscosity of the flame-retardant electrolyte is appropriate, thereby improving the impregnation of the flame-retardant electrolyte.
[0106] In addition, the flame-retardant electrolyte may further include an electrolyte additive as necessary to prevent the electrolyte from being decomposed in a high-power environment, which may cause the negative electrode to collapse, or to improve low-temperature high-rate discharge characteristics, high-temperature stability, overcharge prevention, or battery expansion suppression effect at high temperatures.
[0107] Representative examples of such electrolyte additives include one or more compounds selected from the group consisting of cyclic carbonate compounds, halogen-substituted carbonate compounds, sultone compounds, sulfate compounds, phosphate compounds, borate compounds, nitrile compounds, benzene compounds, amine compounds, silane compounds, and lithium salt compounds.
[0108] Among these, the cyclic carbonate compounds include vinylene carbonate (VC) or vinylethylene carbonate. The halogen-substituted carbonate compounds include fluoroethylene carbonate (FEC). The sultone compounds include compounds selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethene sultone, 1,3-propene sultone (PRS), 1,4-butene sultone, and 1-methyl-1,3-propene sultone. The sulfate-based compound may be ethylene sulfate (Esa), trimethylene sulfate (TMS), or methyltrimethylene sulfate (MTMS), and the phosphate-based compound may be one or more selected from the group consisting of lithium difluoro(bisoxalato)phosphate, lithium difluorophosphate, tetramethyltrimethylsilylphosphate, and tris(2,2,2-trifluoroethyl)phosphate.
[0109] The borate-based compound may be tetraphenylborate, lithium oxalyl difluoroborate (LiODFB) or lithium bis(oxalate) borate (LiB(C2O4)2, LiBOB), and the nitrile-based compound may be one or more selected from the group consisting of succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanenitrile, cyclopentanecabonitrile, cyclohexanecabonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile. In addition, the benzene-based compound may be fluorobenzene, the amine-based compound may be triethanolamine or ethylenediamine, and the silane-based compound may be tetravinylsilane. The lithium salt-based compound may be a compound different from the lithium salt contained in the flame-retardant electrolyte, and may be lithium nitrate, lithium difluorophosphate (LiDFP), LiPO2F2, or LiBF4.
[0110] The electrolyte additive may be included in an amount of 0.1 to 10 wt %, 0.2 to 8 wt %, or 0.5 to 8 wt % based on the total weight of the flame-retardant electrolyte, and may contribute to improving ion conductivity or cycle characteristics.
[0111] The lithium secondary battery may have a form in which the electrode assembly is housed in a case and the flame-retardant electrolyte is injected and impregnated therein, and may be a cylindrical, square, pouch, or coin type battery depending on the form of the case, etc. In this case, the battery case may be one commonly used in the art, and there is no limitation on the outer shape according to the use of the battery, and may be, for example, a cylindrical, square, pouch, or coin type, but is not limited thereto.
[0112] The lithium secondary battery may be manufactured by placing the electrode assembly in a suitable battery case and then injecting a flame-retardant electrolyte, or may be manufactured by stacking the electrode assemblies, impregnating the stack with a flame-retardant electrolyte, and then placing the stack in a battery case and sealing it.
[0113] The lithium secondary battery described above can be used not only as a battery cell used as a power source for a small device, but also as a unit battery for a medium- to large-sized battery module including a number of battery cells. Preferred examples of the medium- to large-sized device include electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems (ESS).
[0114] The present invention will be described in more detail with reference to the following specific examples. However, the following examples are merely illustrative for understanding the invention and are not intended to limit the scope of the invention.
[0115] <Examples and Comparative Examples> First, in the following examples, the zeta potential of the polymer particles or ceramic particles was measured by electrophoretic light scattering using a dynamic light scattering device (product name: ELS-Z) at a temperature of 25°C, with the polymer particles or ceramic particles dispersed in an aqueous solvent at a concentration of 0.1% by weight or less.
[0116] Example 1 S1: Li(Ni) 0.8 Mn 0.1 Co 0.1 A cathode slurry containing such a cathode active material was applied and dried to form a cathode active material layer. The total thickness of the current collector and the cathode active material layer was 176 μm.
[0117] S2: Primary rolling was performed using a pilot rolling device so that the sum of the thickness of the current collector and the thickness of the positive electrode active material layer was 150 μm, and the porosity of the positive electrode active material layer was 40%. At this time, the porosity of the positive electrode active material layer was calculated from the true density of the positive electrode active material, and the mass, area, and thickness of the positive electrode active material layer according to Equations 1 and 2.
[0118] S3: A coating layer slurry was applied onto the primarily rolled positive electrode active material layer.
[0119] The coating layer slurry was prepared by dispersing polymethyl methacrylate (PMMA) polymer particles having a zeta potential of -50 mV and a particle size of 1 μm in an N-methyl-2-pyrrolidone (NMP) solvent such that the mass ratio of PMMA:hydrogenated nitrile rubber (H-NBR):polyvinylidene fluoride (PVDF) was 7:1:2 (solid content 21 wt%).
[0120] The coating layer slurry was dried to form a positive electrode laminate including a coating layer.
[0121] S4: The positive electrode laminate was subjected to secondary rolling using a pilot rolling device. The secondary rolling was performed so that the porosity of the positive electrode active material layer was 26%, and the total thickness of the positive electrode current collector and the positive electrode active material layer after the secondary rolling was 125 μm.
[0122] S5: A negative electrode was laminated on the coating layer to prepare an electrode assembly.
[0123] The negative electrode used had a copper current collector and contained graphite as the negative electrode active material.
[0124] Comparative Example 1 S1: Carried out in the same manner as in Example 1 above.
[0125] S2: The same procedure as in Example 1 was carried out, except that the primary rolling was performed so that the porosity of the positive electrode active material layer was 26%, and the total thickness of the current collector and the positive electrode active material layer after the primary rolling was 125 μm.
[0126] S3: Carried out in the same manner as in Example 1 above.
[0127] S4: No secondary rolling was performed.
[0128] S5: Carried out in the same manner as in Example 1 above.
[0129] Comparative Example 2 S1: Carried out in the same manner as in Example 1 above.
[0130] S2: The same procedure as in Example 1 was carried out, except that the primary rolling was performed so that the porosity of the positive electrode active material layer was 30%, and the total thickness of the current collector and the positive electrode active material layer after the primary rolling was 132 μm.
[0131] S3: Carried out in the same manner as in Example 1 above.
[0132] S4: The same procedure as in Example 1 was carried out, except that the positive electrode active material layer was subjected to secondary rolling so that the porosity thereof was 26%, and the sum of the thickness of the positive electrode current collector and the thickness of the positive electrode active material layer after the secondary rolling was 125 μm.
[0133] S5: Carried out in the same manner as in Example 1 above.
[0134] Comparative Example 3 S1: Carried out in the same manner as in Example 1 above.
[0135] S2: The same procedure as in Example 1 was carried out, except that the primary rolling was performed so that the porosity of the positive electrode active material layer was 48%, and the total thickness of the current collector and the positive electrode active material layer after the primary rolling was 173 μm.
[0136] S3: Carried out in the same manner as in Example 1 above.
[0137] S4: The same procedure as in Example 1 was carried out, except that the positive electrode active material layer was subjected to secondary rolling so that the porosity thereof was 26%, and the sum of the thickness of the positive electrode current collector and the thickness of the positive electrode active material layer after the secondary rolling was 125 μm.
[0138] S5: Carried out in the same manner as in Example 1 above.
[0139] Comparative Example 4 S1: Carried out in the same manner as in Example 1 above.
[0140] S2: No primary rolling was performed.
[0141] S3: Carried out in the same manner as in Example 1 above.
[0142] S4: The same procedure as in Example 1 was carried out, except that the positive electrode active material layer was rolled to have a porosity of 26%, and the sum of the thickness of the positive electrode current collector after the rolling and the thickness of the positive electrode active material layer was 125 μm.
[0143] S5: Carried out in the same manner as in Example 1 above.
[0144] <Experimental Example 1> Check for damage to the electrode assembly The electrode assemblies manufactured in Example 1 and Comparative Examples 1 to 4 were visually inspected for damage and judged as follows. The measurement results are shown in Table 1 below.
[0145] The presence or absence of damage to the electrode assembly was determined by visually checking whether waviness occurred at the boundary between the region of the electrode assembly where the positive electrode active material layer was formed after the first rolling in step (S2) and the current collector region where the positive electrode active material layer was not formed. If waviness occurred, it was determined that the electrode assembly was damaged.
[0146] In addition, it was visually determined whether or not cracks occurred on the surface of the coating layer. If cracks occurred, it was determined that the electrode assembly was damaged.
[0147] O: Waviness is observed on the current collector or cracks are observed on the surface of the coating layer.
[0148] X: No waviness was observed on the current collector, and no cracks were observed on the surface of the coating layer.
[0149] [Table 1]
[0150] In the case of Example 1, no waviness was observed at the boundary between the region where the positive electrode active material layer was formed after the first rolling in step (S2) and the current collector region where the positive electrode active material layer was not formed, and no cracks were found in the coating layer.
[0151] In the case of Comparative Example 1 and Comparative Example 2, waviness occurred at the boundary between the region where the positive electrode active material layer was formed after the primary rolling in step (S2) and the current collector region where the positive electrode active material layer was not formed.
[0152] In the case of Comparative Example 3, no waviness was found in step (S2), but the organic solvent of the coating layer slurry penetrated into the positive active material layer when the coating layer slurry was applied onto the positive active material layer that had been subjected to the first rolling in step (S3), causing the positive active material layer to easily detach from the electrode assembly, and cracks were found on the surface of the dried coating layer.
[0153] In the case of Comparative Example 4, no waviness was found in step (S2), but the organic solvent of the coating layer slurry penetrated into the positive active material layer when the coating layer slurry was applied onto the positive active material layer in step (S3), which caused the positive active material layer to easily detach from the electrode assembly, and cracks were found on the surface of the dried coating layer.
[0154] <Experimental Example 2> Check the thickness of the mixed layer of the electrode assembly The thickness of the mixed layer was confirmed from photographs of the cross sections of the positive electrode and the coating layer of Example 1 and Comparative Example 4 taken using a scanning electron microscope (SEM).
[0155] The thickness of the mixed layer was defined as the maximum depth of the coating layer penetrating into the positive electrode active material layer from the boundary between the positive electrode active material layer and the coating layer in a photograph of the cross section of the positive electrode and the coating layer.
[0156] SEM photographs of Example 1 and Comparative Example 4 are shown in FIG. 1 and FIG. 2, respectively, and the measured thicknesses of the mixed layers of Example 1 and Comparative Example 4 are shown in Table 2 below.
[0157] [Table 2]
[0158] Unlike Comparative Example 4, Example 1 was subjected to primary rolling so that the positive electrode active material layer had an appropriate porosity. It was confirmed that in Example 1, a mixed layer in which the positive electrode active material layer and the coating layer were mixed was present only in a very thin thickness.
Claims
1. (S1) applying a positive electrode slurry onto a positive electrode current collector and drying the slurry to form a positive electrode active material layer; (S2) primarily rolling the positive electrode current collector and the positive electrode active material layer; (S3) applying a coating layer slurry onto the positive electrode active material layer and drying it to form a positive electrode laminate including a coating layer; (S4) subjecting the positive electrode laminate to a second rolling process; (S5) laminating a negative electrode on the coating layer to manufacture an electrode assembly; A method for manufacturing an electrode assembly, wherein the first rolling step is performed so that a porosity of the positive electrode active material layer is 35% to 45%, and the second rolling step is performed so that a porosity of the positive electrode active material layer is 20% to 30%.
2. 2. The method of claim 1, wherein the coating layer slurry comprises a polymer binder, polymer particles or ceramic particles having an absolute value of a zeta potential of 25 mV or more, and a liquid medium.
3. 3. The method of claim 2, wherein the coating layer slurry comprises the polymer binder:the polymer particles or ceramic particles in a weight ratio of 5:95 to 40:
60.
4. The method of claim 2 , wherein the polymer particles or ceramic particles have a particle size of 50 nm to 3 μm.
5. 2. The method of claim 1, wherein a total thickness of the positive electrode current collector and the positive electrode active material layer after the first rolling is 80% to 90% of a total thickness of the positive electrode current collector and the positive electrode active material layer before the first rolling.
6. 6. The method for manufacturing an electrode assembly according to claim 1, wherein a total thickness of the positive electrode current collector and the positive electrode active material layer after the second rolling is 60% to 75% of a total thickness of the positive electrode current collector and the positive electrode active material layer before the first rolling.
7. The method of claim 2 , further comprising the step of adjusting the absolute value of the zeta potential to 25 mV or more by plasma treating polymer particles or ceramic particles.
8. A positive electrode current collector; a positive electrode active material layer disposed on the positive electrode current collector; a coating layer coated on the positive electrode active material layer; a mixed layer in which the positive electrode active material layer and the coating layer are mixed; a negative electrode disposed on the coating layer, the negative electrode including a negative electrode current collector and a negative electrode active material layer; The coating layer and the mixed layer each include a polymer binder and polymer particles or ceramic particles having an absolute value of a zeta potential of 25 mV or more dispersed on the polymer binder, and the mixed layer has a thickness of less than 15 μm.
9. 9. The electrode assembly of claim 8, wherein the thickness of the mixed layer is 5 to 14 μm, and the sum of the thickness of the mixed layer and the coating layer is 5 to 50 μm.
10. The electrode assembly of claim 8 , wherein the polymer particles or ceramic particles have a particle size of 50 nm to 3 μm.
11. 9. The electrode assembly of claim 8, wherein the coating layer and the mixed layer comprise the polymer binder:the polymer particles or ceramic particles in a weight ratio of 5:95 to 40:
60.
12. 9. The electrode assembly of claim 8, wherein the polymer particles include at least one selected from the group consisting of polymethyl (meth)acrylate, polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate, polyethylene terephthalate, and polyphenylene sulfide.
13. 9. The electrode assembly of claim 8, wherein the ceramic particles include one or more selected from the group consisting of boehmite, aluminum oxide, titanium oxide, iron oxide, silicon oxide, zirconium oxide, cobalt oxide, tin oxide, nickel oxide, zinc oxide, vanadium oxide, and manganese oxide.
14. A lithium secondary battery comprising: a battery case; a flame-retardant solvent having a flash point of 100° C. or more or having no flash point; a flame-retardant electrolyte containing a lithium salt; and the electrode assembly according to any one of claims 8 to 13.
15. 15. The lithium secondary battery according to claim 14, wherein the flame-retardant solvent comprises one or more organic solvents selected from the group consisting of sulfone-based compounds, nitrile-based compounds, phosphoric acid-based compounds, and fluorine-substituted carbonate-based compounds.
Citation Information
Patent Citations
Solid electrolyte film, positive electrode film or negative electrode film for all-solid lithium secondary battery, forming method of these films, and all-solid lithium secondary battery
JP2009176541A
Negative electrode, lithium ion secondary battery, method for manufacturing negative electrode for lithium ion secondary battery, and method for manufacturing negative electrode sheet for lithium ion secondary battery
JP2021197249A
Method for manufacturing battery
JP2022024888A
Lithium ion secondary battery
WO2005011043A1